The Benefits of Daily Work Experience in Enhancing the Hospitality Skills of Students at Vocational High School Palembang - Anton; Margriet Puspa Dewi; Akhmad Khudri (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to analyse the benefits of the Daily Worker program in enhancing hospitality students’ skills, particularly in terms of mental readiness, time management, and both technical and non-technical competencies. Method: This study employs a qualitative case study approach. Data were collected through in-depth interviews, direct observation, and documentation, and were analysed using thematic and discourse analysis to gain comprehensive insights into students’ experiences. Result: The findings reveal that the Daily Worker program significantly enhances students’ technical skills, such as guest service and the implementation of standard operating procedures, as well as non-technical skills, including communication, teamwork, discipline, responsibility, and mental readiness. The program also fosters professionalism and adaptability in dynamic work environments. Contribution: This study highlights the effectiveness of work-based learning through the Daily Worker program in bridging the gap between school-based learning and industry needs. It provides valuable insights for improving vocational education programs and strengthening collaboration between schools and the hospitality industry.